2015
DOI: 10.1089/scd.2014.0211
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin-1β Induces Mature Ventricular Cardiac Differentiation from Induced Pluripotent Stem Cells Contributing to Cardiac Tissue Repair

Abstract: Stem cell-derived cardiomyocytes (CMs) are often electrophysiologically immature and heterogeneous, which represents a major barrier to their in vitro and in vivo application. Therefore, the purpose of this study was to examine whether Neuregulin-1b (NRG-1b) treatment could enhance in vitro generation of mature ''workingtype'' CMs from induced pluripotent stem (iPS) cells and assess the regenerative effects of these CMs on cardiac tissue after acute myocardial infarction (AMI). With that purpose, adult mouse f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 55 publications
0
27
0
Order By: Relevance
“…Of note, T3 is present in the serum substitute, B-27 (Life Technologies), which is used as a media constituent in multiple directed cardiomyocyte differentiation protocols. Other factors have been reported to promote the maturation of at least some parameters in cardiomyocytes from mouse or human PSCs include neuregulin [119, 120], angiotensin II [63], and the alpha-adrenergic agonist phenylephrine [63]. Finally, while it has been suggested that non-myocytes secrete as yet undefined factors that favor human PSC-derived cardiomyocyte maturation [61], our own data demonstrate that these factors are not absolutely required for maturation [60].…”
Section: Remaining Obstacles To the Successful Translation Of Plurmentioning
confidence: 99%
“…Of note, T3 is present in the serum substitute, B-27 (Life Technologies), which is used as a media constituent in multiple directed cardiomyocyte differentiation protocols. Other factors have been reported to promote the maturation of at least some parameters in cardiomyocytes from mouse or human PSCs include neuregulin [119, 120], angiotensin II [63], and the alpha-adrenergic agonist phenylephrine [63]. Finally, while it has been suggested that non-myocytes secrete as yet undefined factors that favor human PSC-derived cardiomyocyte maturation [61], our own data demonstrate that these factors are not absolutely required for maturation [60].…”
Section: Remaining Obstacles To the Successful Translation Of Plurmentioning
confidence: 99%
“…The advantages and limitations of each stem cell with regard to the possible emergence of ethical concerns (symbolized by ¥), the invasiveness and collection (from + to ++++), the isolation procedure, the abundance (from + to ++++), expansion and proliferation rate, the transdifferentiation capacity, the paracrine effects or/and cardiomyogenic potential, the survival and engraftment capacity as well as the immunogenic, oncogenic or teratogenic risks is given in the accessory side tables. The left table abridges bone marrow-derived stem cells [3,[19][20][21]27,28], cortical bone-derived stem cells [32,33], adipose tissue-derived stem cells [34,37,39,41] and gestation-related stem cells [42][43][44][45][46][47][48][49]51,54] and the right table abridges cardiac stem cells [57,59,60], skeletal muscle stem cells [62,63,66] and induced pluripotent stem cells [67,[69][70][71]. The human body scheme was constructed with images sourced from Servier Medical Art (http://www.servier.com/ Powerpoint-image-bank) and Cientic website (http://www.cientic.com/).…”
Section: Adipose Tissue-derived Stem Cellsmentioning
confidence: 99%
“…Virtually, all adult cells can be subjected to a dedifferentiation program with a set of stemness factors to become induced pluripotent stem cells (iPSC) [67][68][69]. If not collected from an autologous source, iPSC are related to immunogenic and teratogenic risks (Fig.…”
Section: Induced Pluripotent Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NRG-1β isoform of NRG has effects on cardiomyocyte survival as well as structure and function in vitro, in addition to endothelial cell and fibroblast responses 42,43 . In addition, NRG-1β activates differentiation of progenitor cell populations toward cardiac cell lineages, at least in vitro 44,45 . Some or all of these effects may explain how recombinant NRG-1β given to both animals and humans with systolic dysfunction is associated with improvements in heart function.…”
Section: Introductionmentioning
confidence: 99%